Interleukin-9 protects from early podocyte injury and progressive glomerulosclerosis in Adriamycin-induced nephropathy - Xiong, Tingting; Attar, Madena; Gnirck, Ann Christin; Wunderlich, Malte; Becker, Martina; Rickassel, Constantin; Puelles, Victor G.; Meyer-Schwesinger, Catherine; Wiech, Thorsten; Nies, Jasper F.; Divivier, Mylène; Fuchs, Tobias; et al. (Kidney International, 2020)
A wide spectrum of immunological functions has been attributed to Interleukin 9 (IL-9), including effects on the survival and proliferation of immune and parenchymal cells. In recent years, emerging evidence suggests that IL-9 expression can promote tissue repair in inflammatory conditions. However, data about the involvement of IL-9 in kidney tissue protection is very limited. Here, we investigated the role of IL-9 in Adriamycin-induced nephropathy (AN), a mouse model for proteinuric chronic kidney disease. Compared to wild type mice, IL-9 knockout (Il9−/−) mice with AN displayed accelerated development of proteinuria, aggravated glomerulosclerosis and deterioration of kidney function. At an early stage of disease, the Il9−/− mice already displayed a higher extent of glomerular podocyte injury and loss of podocyte number compared to wild type mice. In the kidney, T cells and innate lymphoid cells produced IL-9. However, selective deficiency of IL-9 in the innate immune system in Il9−/−Rag2−/− mice that lack T and B cells did not alter the outcome of AN, indicating that IL-9 derived from the adaptive immune system was the major driver of tissue protection in this model. Mechanistically, we could show that podocytes expressed the IL-9 receptor in vivo and that IL-9 signaling protects podocytes from Adriamycin-induced apoptosis in vitro. Finally, in vivo treatment with IL-9 effectively protected wild type mice from glomerulosclerosis and kidney failure in the AN model. The detection of increased serum IL-9 levels in patients with primary focal and segmental glomerulosclerosis further suggests that IL-9 production is induced by glomerular injury in humans. Thus, IL-9 confers protection against experimental glomerulosclerosis, identifying the IL-9 pathway as a potential therapeutic target in proteinuric chronic kidney disease.
CRIS-Team Scopus Importer:2020-08-14
Keywords: cytokines; focal segmental glomerulosclerosis; inflammation; lymphocytes